Componentes de riesgo psicosocial y satisfacción laboral en enfermeras de un Hospital de Cajamarca, Perú. - Aliaga-Zamora, G.J. (2022)
Introduction: Psychosocial risk components and job satisfaction are relevant for nurses. Mental workload, psychobiological instabilities, decision-making and control process, as well as variability, constitute psychological aspects. On the other hand, social risks, work organization and responsibility, timely information, training and working hours are part of the setting. Objective: To establish the degree of association between psychosocial risk components and job satisfaction in nurses of Hospital Regional de Cajamarca. Methods: Quantitative, correlational, cross-sectional and descriptive study carried out at Hospital Regional de Cajamarca, Peru, during August-December 2018. The population was made up of 241 nurses. A total of 148 nurses were selected by simple random sampling. A battery of instruments for the evaluation of psychosocial risk components was applied: BIPEFRPS and the Job Satisfaction Scale, both adapted by experts and validated using a pilot test. The data were processed with IBM-SPSS V.25. Percentage was used, while the rho Spearman correlation statistic was used for the hypothesis testing (p<0.05, statistical significance). Results: A significant (p<0.05) and negative (r=0.224) degree of association was evidenced between the components of psychosocial risk and job satisfaction in nurses. Conclusions: Psychosocial risk components have a negative degree of association with job satisfaction. Thus, control of psychosocial risk components increases levels of job satisfaction.